Analysis of simple sequence repeat (SSR) polymorphism between N22 and Uma rice varieties for marker assisted selection - Swapnil Gorakh Waghmare; P. Sindhumole; M. R. Shylaja; Deepu Mathew; Rose Mary Francies; P. S. Abida and; S. Sajini (Electronic Journal of Plant Breeding, 2018)
SSR polymorphism in two rice varieties viz., N22 (donor parent for heat and drought tolerance) and Uma (high yielding variety susceptible to heat and drought) was investigated to identify ready to use SSR markers which can be employed in selection in the marker assisted breeding programmes involving these varieties. For this, 197 simple sequence repeat (SSR) primers which were distributed on all the twelve chromosomes of rice were utilised. The results revealed distinct polymorphism among the tolerant and susceptible parents for 41 RM primers. Based on this study, the large range of similarity and dissimilarity values for N22 and Uma provides greater confidence for the assessment of simple sequence repeat (SSR) polymorphism. Diversity analysis can be done by using these polymorphic SSR markers. These polymorphic markers can also be used for the linkage analysis of various traits. Besides, these identified polymorphic SSR markers can be utilised for QTL mapping by screening the progenies of the cross Uma × N22.